2008
DOI: 10.21273/jashs.133.3.374
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Seven Deciduous Azalea Species (Rhododendron spp. section Pentanthera) Native to the Eastern United States

Abstract: Despite the ecologic and economic importance of native deciduous azaleas (Rhododendron L. section Pentanthera G. Don), our understanding of interspecific variation of North American deciduous azalea species comes principally from morphologic studies. Furthermore, little is known concerning intraspecific or interpopulation genetic variation. With ever-increasing loss and fragmentation of native azalea habitat in the eastern United States due to anthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…An analysis of R. canescens genetic diversity was included in a prior study (Chappell et al, 2008) that examined four R. canescens populations (six accessions each) with AFLP markers. Similar to that study, our investigation found a low G ST value, indicating that the proportion of diversity between populations was low, while the proportion of diversity within populations was high.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An analysis of R. canescens genetic diversity was included in a prior study (Chappell et al, 2008) that examined four R. canescens populations (six accessions each) with AFLP markers. Similar to that study, our investigation found a low G ST value, indicating that the proportion of diversity between populations was low, while the proportion of diversity within populations was high.…”
Section: Discussionmentioning
confidence: 99%
“…Minimal differentiation between R. canescens populations was also indicated by the low F ST value. Chappell et al (2008) suggested that this may be the result of gene flow between populations due to insect pollination. R. canescens is known to be pollinated by bumblebees, adrenid bees, butterflies, and hummingbirds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Zhang et al, 2010), sweetpotato [Ipomoea batatas (Cervantes-Flores et al, 2008)], pecan [Carya illinoinensis (Beedanagari et al, 2005)], Rhododendron sp. (Chappell et al, 2008), barberry [Berberis thunbergii (Lubell et al, 2009)], and Lactuca sp. (Koopman et al, 2001).…”
mentioning
confidence: 99%